Factors Influencing Participation Of Rural Women In Padzey Project In Taiz Governorate, Yemen - Abdul Wahib Al-Areqi, Belqes Mutahar (2010)

(untitled)
The rural women in Yemen have many roles to play in their lives and are mainly responsible for livestock and cheese production. The ‘Projet d’Appui au Développement des Zones d’Elevage du Yemen’- PADZEY under the auspices of the AFD Group (Agence Francaise de Développement ) which was a project under the French Ministry for Cooperation with the Government of Yemen under the PFD – Partnership Framework Document for the period 2007-2011, spearheaded to increase the income generated from livestock production of small farmers in the project areas. This study was designed to examine rural women’s participation in the PADZEY project and determine the factors that affect variation level of participation in the PADZEY project. The research employed quantitative data collection through administered interview by using a questionnaire. The respondents comprised of 172 of rural women who were stratified random sampling from three districts in Taiz government in Yemen. A Descriptive Analysis, Pearson Product Moment Correlation, and Multiple Regression Analyses were used to analyse the data. Rural women’s iv participation in PADZEY project was measured using the composite score for participation in decision-making, participation in implementation, participation in evaluation and participation in benefits. The findings of this study showed that the level of respondent’s participation was moderately low in the PADZEY project, illustrating moderately low level of rural women’s knowledge in the PADZEY project and skills of livestock production. However, they indicated positive and moderately high level of attitude towards the PADZEY project. The rural women’s participation in the PADZEY project was significantly correlated with monthly income, knowledge in the PADZEY project, skills of livestock production, and attitude towards the PADZEY project. Meanwhile age, number of family member, and experience of livestock production showed no significant correlation with participation. However, regression analyses showed that the variance, in the rural women’s participation in the PADZEY project explained by the independent variables, was moderately high (68.8%). This moderately high result may be due to the fact that these variables (skills of livestock production and attitudes towards the PADZEY project) were the main factors affecting participation. The result of this study provided practical implications and recommendation to increase the level of participation in the PADZEY project.